Shaykh 'Abd al-Samad al-Palimbani's understanding of tawhid - Muchtar, Ali
The present research is an attempt to explicate Shaykh 'Abd al-Samad al-Palimbani's understanding of tawhid, which to Muslims is a very pivotal matter in terms of both its doctrine and practice. Shaykh 'Abd al-Samad al-Palimbani (d. ca. 1243/1828) was one of the Malay thinkers who wrote prolifically on many subjects and was known as the most prominent 'translator' of al-Ghazali's teachings in the Malay world. Here, the discourse of tawhid has become a matter of debate since the early 16th century. Many people have been confused in their understanding of tawhid because of their lack of knowledge on the essential teachings of Islam. Thus, it is important to seek an explanation of 'Abd al-Samad's views on tawhid in dealing with religious problems in his community, and how he propagated his understanding based on the teachings of the Sunni school. In this study, the approach that has been adopted is textual analysis, using descriptive and analytical methods from various works on the subject. It seeks to discover how 'Abd al-Samad elaborated his understanding of tawhid in his time. It is concluded that his understanding of tawhid is in line with the teachings of the Ahl sunnah wa al-jama'ah. However, some scholars criticize his thought and say that it has an inclination toward Ibn'Arabi's school of thought. 'Abd al-Samad al-Palimbani attempted to solve the intellectual and religious problems faced by the Malays during his time by reconciling the tradition of Ibn 'Arabi with al-Ghazali's. He succeeded in harmonizing the two schools of thought as well as in synthesizing the theological approach with the Sufi tradition.